2009
DOI: 10.1158/0008-5472.sabcs-34
|View full text |Cite
|
Sign up to set email alerts
|

PI3 kinase activation and response to trastuzumab or lapatinib in HER-2 overexpressing locally advanced breast cancer (LABC).

Abstract: #34 Background: Activating mutations of PI3 kinase (PIK3CA) and PTEN loss may be associated with trastuzumab resistance. Trastuzumab, a HER2 humanized monoclonal antibody, and lapatinib, an EGFR/HER2 tyrosine kinase inhibitor are both established treatments. Greater understanding of the cellular response to trastuzumab or lapatinib is needed to tailor targeted therapy for individual patients and identify those less likely to benefit. Material and Methods: We performed two sequential neoadjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Moreover, different modes of cellular drug resistance have been suggested for trastuzumab and lapatinib and this underlines the rationale of lapatinib administration after trastuzumab failure 56 . However, some BCs do not respond or develop resistance to lapatinib too (e.g.…”
Section: Resistance To Lapatinibmentioning
confidence: 99%
“…Moreover, different modes of cellular drug resistance have been suggested for trastuzumab and lapatinib and this underlines the rationale of lapatinib administration after trastuzumab failure 56 . However, some BCs do not respond or develop resistance to lapatinib too (e.g.…”
Section: Resistance To Lapatinibmentioning
confidence: 99%
“…However, lapatinib inhibits growth of trastuzumab-resistant breast cancer cells (5,6) and shows clinical efficacy in patients who have received prior therapy with an anthracycline, a taxane, and trastuzumab (1). Moreover, low PTEN expression or PIK3CA mutations did not preclude response to lapatinib in primary tumors from women with HER2-overexpressing locally advanced breast cancer who received 6 weeks of lapatinib monotherapy before standard neoadjuvant treatment (7). Multiple mechanisms of resistance have been reported for tyrosine kinase inhibitors that selectively target HER1, such as gefitinib and erlotinib.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to changes following anti-HER2 therapy, change in tumour size after 11 days of therapy may provide additional prognostic information that is not available from a pretreatment tumour specimen. Lapatinib has been reported [20] to shrink tumour size by 74% after 6 weeks which interpolates to a 36% shrinkage after 2 weeks. Moshin et al [21] also found early tumour regression with a median decrease of 20% (0-60.4%) after 3 weeks of trastuzumab; changes in apoptosis were also observed over this period.…”
Section: The Potential Gain Of Prognostic and Predictive Informationmentioning
confidence: 89%
“…There is some evidence that anti-HER2 therapy, unlike chemotherapy, is effective against stem cells. Rodriguez et al [20] carried out a presurgical study involving 45 patients which provided evidence suggesting that lapatinib decreases breast cancer stem cells in the primary breast cancers of women receiving presurgical lapatinib.…”
Section: Evidence For the Biological Effect Of Anti-her2 Therapymentioning
confidence: 99%